Transfer RNA-derived small RNAs (tsRNAs): A rising star in liquid biopsy - Qinglin Wang; Zehao Pan; Si Liang; Yuanjian Shi; Gaochao Dong; Lin Xu; Qixing Mao; Feng Jiang (Genes and Diseases)
Liquid biopsy has emerged as a valuable clinical tool due to its non-invasive nature and real-time molecular profiling capabilities. Transfer RNA-derived small RNAs (tsRNAs) are a group of small non-coding RNAs generated from mature tRNAs or tRNA precursors. Recently, increasing studies have reported tsRNAs' potential to serve as promising biomarkers in various diseases, especially cancers. Notably, tsRNAs can be detected in various kinds of body fluids, such as seminal fluid plasma, blood plasma, saliva, and urine, and have been demonstrated to exist stably in body fluids. In this mini-review, we will summarize the recent discoveries on the role of tsRNAs in body fluids as biomarkers, hoping to provide new insights for disease diagnosis and therapeutic strategies.